Phenotypic variability in Rett syndrome associated with FOXG1 mutations in females. Issue 1 (29th June 2009) - Philippe, C; Amsallem, D; Francannet, C; Lambert, L; Saunier, A; Verneau, F; Jonveaux, P
Abstract : Background: The FOXG1 gene has been recently implicated in the congenital form of Rett syndrome (RTT). It encodes the fork-head box protein G1, a winged-helix transcriptional repressor with expression restricted to testis and brain, where it is critical for forebrain development. So far, only two point mutations in FOXG1 have been reported in females affected by the congenital form of RTT. Aim: To assess the involvement of FOXG1 in the molecular aetiology of classical RTT and related disorders. Methods: The entire multi-exon coding sequence of FOXG1 was screened for point mutations and large rearrangements in a cohort of 35 MECP2/CDKL5 mutation-negative female patients including 31 classical and four congenital forms of RTT. Results: Two different de novo heterozygous FOXG1 -truncating mutations were identified. The subject with the p.Trp308X mutation presented with a severe RTT-like neurodevelopmental disorder, whereas the p.Tyr400X allele was associated with a classical clinical RTT presentation. Conclusions: These new cases give additional support to the genetic heterogeneity in RTT and help to delineate the clinical spectrum of the FOXG1 -related phenotypes. FOXG1 screening should be considered in the molecular diagnosis of RTT.